Analisis implementasi wakaf wasiat polis asuransi syariah di lembaga wakaf al-Azhar Jakarta - Siska Lis Sulistiani (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2017)
Waqf in Islam is one way to invest in property for the sake of the world and the hereafter. The development of waqaf must still be in the sharia corridor so that its ubudiyah and iqtishadiyah values remain. Islamic law will not be known even as DSN MUI has just released its fatwa in October 2016 which is the investment benefit and sharia life fatwa, but some sharia insurance institutions and wakaf institutions in Indonesia first applied this form of waqf. The legal status of a wakaf law on Islamic insurance policy under Islamic law includes productive wakaf. However, in terms of its ownership element as a waqf object has not been fully owned by wakif so ulama differed in opinion, although in principle has been owned by wakif, but still opens the dispute space because the waqf object is not yet fully owned. The wakaf law of syariah insurance policy itself is still potentially canceled by wakif or by sharia insurance if one of them wakif get difficulty paying the premium before maturity. Implementation of waqf syariah insurance policy at Al-Azhar Wakaf Institute Jakarta has not yet fully complied with the rules of Fatwa DSN MUI because the fatwa has just come out in the end of 2016 and socialized in early 2017, whereas the wakaf will be known as sharia insurance policy in the community.